The Development and Intellectualisation of African Languages Revisited. - Ndoleriire, Oswald Kyamulesire (Kabale University, 2024)
In this article, I am revisiting, the well-known topic of developing African languages and the concept of the intellectualisation of African languages. I start by defining the idea of intellectualisation which involves using a language in all areas of human endeavour. I then look at some success stories regarding language intellectualisation, in particular the case of Hebrew and Afrikaans. Thereafter, the case of intellectualising languages in Asia reveals a situation where the exercise was quite successful in the case of Malay in Indonesia and Malaysia but less successful with Tagalog converting into Filipino in the Philippines. The case of India is of particular interest to Africa due to a common colonial heritage and the multiplicity of languages because the Indian experience has been relatively successful. In Africa, the commendable efforts in formulating and to some extent implementing an enabling language policy in South Africa are pointed out. A quick review is then carried out on the language situation in some other countries of Sub-Saharan Africa, where the situation leaves a lot to be desired, apart from the glimmer of hope presented by Kiswahili in Eastern Africa. Among the challenges faced by those who want to promote and intellectualise African languages, the issue of the Africans’ mindset and the phenomenon of globalization, with English as one of the globalising agents, are highlighted. Finally, strategies to counter the challenges are proposed, including political will, appropriate policies and the creation of universities using only African languages as media of instruction.